Ketoconazole as second-line treatment for Cushing’s disease after transsphenoidal surgery: systematic review and meta-analysis - Viecceli, Camila; Mattos, Ana Carolina Viana; Hirakata, Vânia Naomi; Garcia, Sheila Piccoli; Rodrigues, Ticiana da Costa; Czepielewski, Mauro Antônio (Frontiers in Endocrinology, 2023)
Introduction The first-line treatment for Cushing’s disease is transsphenoidal surgery for pituitary tumor resection. Ketoconazole has been used as a second-line drug despite limited data on its safety and efficacy for this purpose. The objective of this meta-analysis was to analyze hypercortisolism control in patients who used ketoconazole as a second-line treatment after transsphenoidal surgery, in addition to other clinical and laboratory criteria that could be related to therapeutic response. Methods We searched for articles that evaluated ketoconazole use in Cushing’s disease after transsphenoidal surgery. The search strategies were applied to MEDLINE, EMBASE, and SciELO. Independent reviewers assessed study eligibility and quality and extracted data on hypercortisolism control and related variables such as therapeutic dose, time, and urinary cortisol levels. Results After applying the exclusion criteria, 10 articles (one prospective and nine retrospective studies, totaling 270 patients) were included for complete data analysis. We found no publication bias regarding reported biochemical control or no biochemical control (p = 0.06 and p = 0.42 respectively). Of 270 patients, biochemical control of hypercortisolism occurred in 151 (63%, 95% CI 50-74%) and no biochemical control occurred in 61 (20%, 95% CI 10-35%). According to the meta-regression, neither the final dose, treatment duration, nor initial serum cortisol levels were associated with biochemical control of hypercortisolism. Conclusion Ketoconazole can be considered a safe and efficacious option for Cushing’s disease treatment after pituitary surgery. Systematic review registration https://www.crd.york.ac.uk/prospero/#searchadvanced, (CRD42022308041).